The psychometric characteristics of The Revised Lithuanian Employee Psychological Empowerment Questionnaire (LPEQ–9) - Tvarijonavičius, Mantas; Bagdžiūnienė, Dalia; Žukauskaitė, Irena (Psichologija, 2017)
The psychological empowerment of employees as the psychological enabling and positive motivational state of individuals at work has been broadly studied in relation with their attitudes towards work and organisations, work behaviour, productivity, reactions to changes or innovations. Employee empowerment is especially important for the organisations with flexible management systems which are based on the principles of employee proactivity, personal responsibility and intrinsic work motivation. The article presents the process of improving the LPEQ – Lithuanian Psychological Empowerment Questionnaire (Tvarijonavičius & Bagdžiūnienė, 2013) and the revised 9-item version of the questionnaire. The first version consisted of fifteen items representing five dimensions of psychological empowerment: meaning, enthusiasm, decision making, autonomy, and trust in competence. However, later studies revealed that a three-dimensions exploratory factor solution is also possible (e.g., Jokubauskaitė & Lazauskaitė--Zabielskė, 2016). The aim of the two studies presented in this paper was to repeatedly evaluate and to specify the structure of the LPEQ and to verify the psychometric indicators of the revised 9-item version of the questionnaire. Exploratory and confirmatory factor analyses of data from the first study sample (740 employees from different Lithuanian organisations) were explored to examine the structure, construct validity and reliability of the questionnaire. The CFA showed substantial support for the three factors‘ solution when the first factor (meaning) consisted of two items from the previous meaning dimension and one item from enthusiasm, the second factor (decision making) included two items from the previous decision making and one from autonomy dimensions and the third factor (trust in competence) remained without changes (χ² = 57.69, df = 24, χ² /df = 2.391, p < 0.001; RMSEA = 0.061; GFI = 0.9674; CFI = 0.939; NFI = 0.953). Measures of validity and internal consistency were additionally analysed on the second study data (658 participants). The results proved the convergent validity of the shortened version of the LPEQ: three dimensions and the total score of empowerment were highly and positively related with similar constructs – intrinsic motivation, engagement, autonomy, occupational self-efficacy, in-role behavior (p < 0.01). Cronbach’s α coefficients of the dimensions varied between 0.755 and 0.835.In conclusion, the revised version of the Lithuanian Psychological Empowerment Questionnaire (LPEQ – 9) can be characterised as an instrument with appropriate psychometric properties for use in research and practice. Directions for the future research in the field are discussed.
Keywords: employees; psychological empowerment; revised questionnaire; reliability; validity